Cohabitation--relationships of corynebacteria and staphylococci on human skin - Kwaszewska, Anna; Sobiś-Glinkowska, Maria; Szewczyk, Eligia M (Folia microbiologica, 2014)
Skin microbiome main cultivable aerobes in human are coagulase-negative staphylococci and lipophilic corynebacteria. Staphylococcus strains (155) belonging to 10 species and 105 strains of Corynebacterium belonging to nine species from the skin swabs of healthy male volunteers were investigated to determine their enzymatic activity to main metabolic substrates: carbohydrates, proteins, lipids, and response to factors present on the skin such as osmotic pressure, pH, and organic acids. The results showed that lipophilic corynebacteria have different capacity for adaptation on the skin than staphylococci. Most of Corynebacterium spp. expressed lack of proteinase, phospholipase, and saccharolytic enzymes activity. Corynebacteria were also more sensitive than Staphylococcus spp. to antimicrobial agents existing on human skin, especially to low pH. These characters can explain domination of Staphylococcus genera on healthy human skin. It can be suggested that within these two bacterial genus, there exists conceivable cooperation and reciprocal protection which results in their quantitative ratio. Such behavior must be considered as crucial for the stability of the population on healthy skin.
Keywords: dospělí; Corynebacterium; Bacterial Proteins; Humans; Staphylococcus; Male; Adult; mužské pohlaví; bakteriální proteiny; lidé; Skin; kůže